Implementation Of Multimedia Development Life Cycle Using Android-Based Augmented Reality In Recognition Of Widarapayung Beach Landmark To Increase Tourism Supporting Capacity of Cilacap - Lutfi Syafirullah; Annas Setiawan Prabowo; Abdul Rohman Supriyono; Riyadi Purwanto; Betti Widianingsih; Rostika Listyaningrum; Dodi Satriawan (Evolusi : Jurnal Sains dan Manajemen, 2022)
Abstract               There are many beach tourist destinations in Cilacap Regency, Central Java that can be visited, one of which is Widarapayung beach. Widarapayung Beach is located in Binangun District, Cilacap Regency which is managed under the auspices of the Cilacap Regency Tourism and Culture Office whose implementation is managed by the KODIM 0703 Cilacap Cooperative. The impact of the COVID-19 pandemic and the implementation of the PSBB caused the manager to have difficulty in providing information regarding the facilities available at Widarapayung Beach to potential visitors.                During the pandemic and the implementation of the PSBB, all information publications on Widarapayung beach were limited. Not all information about Widarapayung beach is known by the surrounding community or people from outside Cilacap. One of the multimedia developments that can provide visitors with the introduction of Widarapayung beach landmarks to make it easier to find more interesting information about Widarapayung beach by developing Augmented Reality technology. The result of this research activity is to implement Augmented Reality technology for the introduction of Widarapayung beach landmarks, Cilacap Regency so that visitors can more easily find out the facilities and information in Widarapayung based on Android. Keywords: augmented reality; landmark; widarapayung beach